2020
DOI: 10.1029/2020gl090138
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of the Turbulent Energy Dissipation Beneath Nonbreaking Waves

Abstract: Here we have determined the nature of turbulent flow associated with oceanic nonbreaking waves, which are on average much more prevalent than breaking waves in most wind conditions. We found this flow to be characterized by a low turbulence microscale Reynolds number of 30 < Re < 100. We observed that the turbulent kinetic energy dissipation rate associated with nonbreaking waves , ranged to 3 • 10 −4 W/kg for a wave amplitude 50 cm. The , under nonbreaking waves, was consistent with = 2 T (S i) 2 ; S ij is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 34 publications
4
16
2
Order By: Relevance
“…WW1 and UDM1 as well as WW2 and UDM2 were paired before and after the reef model to ensure the quality of the signals recorded as UDMs may present errors when wave breaking occurs due to the splash of water in the air. Moreover, having two distinct measurements allows also separating incident and reflected waves [31][32][33]. Figure 3 illustrates the experimental setup for this study with the location of the wave gauges.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…WW1 and UDM1 as well as WW2 and UDM2 were paired before and after the reef model to ensure the quality of the signals recorded as UDMs may present errors when wave breaking occurs due to the splash of water in the air. Moreover, having two distinct measurements allows also separating incident and reflected waves [31][32][33]. Figure 3 illustrates the experimental setup for this study with the location of the wave gauges.…”
Section: Methodsmentioning
confidence: 99%
“…Wave heights calculated following the aforementioned process are, however, biased by wave reflection from the artificial parabolic perforated steel beach present at the end of the SUSTAIN flume. Therefore, in this study, incident and reflected waves are separated numerically from their combined signal following [31,32] as the artificial beach in Filtered water-level data were analyzed according to short-term wave theory to calculate wave heights [37,55]. In short-term wave analysis, wave heights are described as the vertical distance between the maximum (wave crest) and minimum (wave trough) water levels between two successive zero-up or down crossings.…”
Section: Institutional Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the standard assumption that the oceanic flow can be approximated by idealized homogenous and isotropic turbulence, the TKED (or ) can be derived from the VMP200 measured shear spectrum Ψ(K) as [25,26]…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The ν T parametrization in terms of measured flow variables permits the effective inclusion of non-breaking waves in models. The experiments of Bogucki et al [11] demonstrated that within the investigated range of wave amplitudes and wavelengths, ν T ≈ 10ν (ν the water molecular kinematic viscosity). Bogucki et al [11] attributed the observed scatter of ν T to the variability of the background turbulent flow but did not provide a parametrization of ν T .…”
Section: Introductionmentioning
confidence: 98%